Self Assembly of Patchy Anisotropic Particle Forming Free Standing Monolayer Film (Adv. Theory Simul. 3/2023). Issue 3 (10th March 2023) - Varma, Vikki Anand; Kritika,; Singh, Jaskaran; Babu, Sujin B.
Abstract : The phase diagram of prolate ellipsoidal particles shows the co‐existence of two types of HCP crystals with the gas particles. Through thermodynamic calculation it is established that a free‐standing monolayer having an HCP arrangement co‐exist with the gas particles in a small region of the phase diagram. This is reported by Sujin B. Babu and co‐workers in article number 2200666 .